Diversity of estrogen biodegradation pathways and application in environmental bioremediation - Hashem, Jaleela S.; Ismail, Wael; Chiang, Yin-Ru; Bekhit, Adnan A. (Frontiers in Microbiology, 2025)
Steroid estrogens, including the naturally occurring hormones estrone (E1), estradiol (E2), and estriol (E3), as well as the synthetic estrogen ethinylestradiol (EE2), play essential physiological roles in the regulation of the reproductive systems and development of secondary sex characteristics in humans and animals. Environmental pollution with steroid estrogens is gaining rising concerns worldwide due to their endocrine-disrupting and carcinogenic properties, which can harm humans and aquatic organisms. Hence, efficient removal of these compounds, particularly from wastewater, is deemed key to prevent environmental pollution with estrogens. Although several physicochemical treatments contribute to estrogen elimination from wastewater treatment plants (WWTPs), biological treatment via microbial biodegradation remains the most efficient estrogen removal approach. Several estrogen-degrading/transforming bacteria were isolated mainly from activated sludge samples collected from WWTPs. Moreover, biochemical, and molecular aspects for estrogen degradation pathways were revealed recently for estrone and estradiol. On the contrary, less knowledge is currently available for E3 and EE2 biodegradation pathways. Despite high structural similarity among steroid estrogens, they can be degraded via a diversity of biodegradation and biotransformation pathways. Nonetheless, these pathways exhibit common as well as unique biochemical and molecular features. Moreover, steroid estrogens are interconvertible, which can affect their environmental concentrations, and hence, their persistence/biodegradability. In this review, we present and discuss the various steroid estrogen biodegradation and biotransformation pathways, with a focus on the biochemical aspects. Furthermore, we highlight some of the known abiotic estrogen reactions and the recent discoveries on microbial estrogenesis and envisage how they can affect estrogen susceptibility to microbial degradation.